KECENDERUNGAN KEMANDIRIAN BELAJAR SISWA SEKOLAH MENENGAH PERTAMA BERDASARKAN FAKTOR DEMOGRAFI - Sunandie Eko Ginanjar, - (2019)
The research point reject the problems that cause a result in students often delaying homework, less responsible and have not been able to make choices. Different abilities determine the readiness of students to participate in learning. The research aims to determine differences in learning autonomy of first-year high school students based on demographic factors. The study was conducted in five schools, namely: Rancaekek Public Middle School, 666 Bhakti Nusantara Private Middle School, 666 Bhakti Nusantara Private Boarding School, Wasilatul Huda Private MTS and Cikancung State MTS. Research participants numbered 450 students. Data taking uses a Likert scale of learning autonomy questionnaire, based on Steinberg's (2002) theory of behavioral aspects, emotional aspects and aspects of values in demographics namely gender, age, place of residence and parents' work. The research findings show there is no learning autonomy based on parents' work, gender and age, whereas based on the place of residence there is a significant difference in learning autonomy.